Effects of Early Development of Hyponatremia on In-hospital Outcomes in Acute ST- Elevation Myocardial Infarction (Bangladesh Heart Journal, 2017)
Background: Coronary heart disease is a major cause of death and is a global health problem and reaching epidemic in both developed and as well as in developing countries. In patients with acute myocardial infarction baroreceptor mediated hormonal activation has a prognostic value. Clinical importance of hyponatraemia in ST-elevation acute myocardial infarction has not been fully understood. Hyponatremia which developed in early phase of AMI has been recently advocated as an important prognostic factor in several studies.Objectives: The aim of the study was to investigate the impact of hyponatremia on in-hospital outcomes in patients with ST-elevation acute myocardial Infarction treated by thrombolysis.Methods: Hyponartaemia was defined as a sodium concentration